PELAYANAN SOSIAL EKONOMI MASJID SKALA LINGKUNGAN KECAMATAN PADANG UTARA - Hadian Resky Aisyah (JURNAL BUANA, 2022)
The purpose of this research is (1) to determine the distribution of neighborhood mosque and the poor society around the neighborhood mosque. (2) analyze the mosque socio economic service programs that have been and never been do. (3) Analyze the range of socio economic service of neighborhood mosque in Kecamatan Padang Utara. The research method used is mixed method with a concurrent design. The data analysis technique used network analyst and the Miles and Huberman data analysis model. The results of this study are (1) the distribution of neighborhood mosques and the surrounding poor, there are still poor people who don’t receivee socio-economic services. (2) the socio-economic mosque service program that has been do by the mosque in general is still conventional services. (3) the comparison between of socio economic service of neighborhood mosque according to the range of theoritical 400 meters and fiels survey in each Kelurahan was varies.